Determinants Of Customer Satisfaction - Narayanan, Satya (2004)
Although various studies undertaken to understand customer satisfaction and loyalty and the extend on how it has influence towards profits, there has not been much studies to understand the attributes that impacts the customer satisfaction. This is an explorative research in further the understanding of the various attributes that has strongest relationship in driving the overall customer satisfaction measurements.